2005
DOI: 10.2174/1568026053544579
|View full text |Cite
|
Sign up to set email alerts
|

The Function of the Extracellular Regions in Opioid Receptor Binding: Insights from Computational Biology

Abstract: Pain management using opioid analgesics strives to achieve three goals: maximum efficacy, minimal risk of tolerance and physical dependence, and negligible side effects. Following the cloning of opioid and nociceptin receptors, novel ligands can be designed to target specific residues of these membrane proteins with the goal of improving efficacy and reducing side effects through selectivity. For the most part, ligand design has focused on binding sites located in the transmembrane region of the receptors, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…However, a large number of GPCRs have large endogenous ligands and those molecules do not easily fit into a hydrophobic binding pocket first described for β-adrenoceptor. In fact, it has been shown that for peptide receptors, such as the opioid receptors, the endogenous ligands, including enkephalins, endorphins and dynorphins appear to primarily bind to orthosteric domains in the extracellular loops of the receptors [46-49]. For example, dynorphin A, the endogenous ligand for the kappa opioid receptor has been shown by mutagenesis studies, NMR analysis and molecular modeling to bind to the second extracellular loop of the kappa receptor [49-54].…”
Section: Crystal Structure and Physical Analysis Of Gpcrsmentioning
confidence: 99%
“…However, a large number of GPCRs have large endogenous ligands and those molecules do not easily fit into a hydrophobic binding pocket first described for β-adrenoceptor. In fact, it has been shown that for peptide receptors, such as the opioid receptors, the endogenous ligands, including enkephalins, endorphins and dynorphins appear to primarily bind to orthosteric domains in the extracellular loops of the receptors [46-49]. For example, dynorphin A, the endogenous ligand for the kappa opioid receptor has been shown by mutagenesis studies, NMR analysis and molecular modeling to bind to the second extracellular loop of the kappa receptor [49-54].…”
Section: Crystal Structure and Physical Analysis Of Gpcrsmentioning
confidence: 99%
“…For example, for the -opioid receptor, there is evidence that extracellular loop regions form part of the binding site for ligands. 53 Loop conformations can be generated using homology modeling, database searching, or ab initio computational methods. A comprehensive review of the loop modeling literature is beyond the scope of this article.…”
Section: Modeling Loop Regionsmentioning
confidence: 99%
“…The three main opioid receptors (μ, δ, κ) 14 show a high degree of sequence homology, and a common opioid receptor binding pocket within a helical transmembrane core. 15,16 The main differences in sequence between the receptors occur in the extracellular domains which contributes to ligand selectivity. 17 The opioid peptides reduce intracellular cAMP by inhibiting adenylate cyclase.…”
Section: Introductionmentioning
confidence: 99%